Online Stress Measurement During Laser-aided Metallic Additive Manufacturing - Yi Lu (Nature Portfolio, 2019)
Abstract In situ measurement of residual stress is a challenge, and it is a source of many defects during additive manufacturing (AM). Usually, postmortem measurement is too late to save the product once a defect appears. Most of the existing technologies are predictive simulations and postmortem analysis. However, these technologies cannot directly reflect the stress evolution during the fabrication process. This paper introduces a computer vision-based stress monitoring system combined with finite element method (FEM) technology to estimate the stress development inside of the deposition layer. The system uses a CCD camera and a line laser beam to measure the height of the melt pool and solidified layer, forms a real-time FEM model, and uses the surface displacement between the two states to calculate the stress development during the solidification process. The results show that there is no obvious shape change after solidification. The shape of the melt pool and its solid state is similar. The stress distribution obtained through online monitoring is similar to that from the traditional thermal-stress simulation.